Does more education lead to better startup funding outcomes? - Craig R. Everett (Cogent Economics & Finance, 2024)
Much of the extant research on the relationship between founder education level and entrepreneurial success finds that more education is associated with increased success. Using a unique data set of startups from a large startup competition, this paper specifically explores funding success and empirically confirms that more education is associated with an increased likelihood of funding. Additionally, we also find a negative curvilinear aspect to that relationship, meaning that although education generally improves funding, too much education may actually impair funding outcomes. Portrayals of startup founders in entertainment media often show scrappy university dropouts battling to get funding - and then finally bringing their new product successfully to market. This article asks and answers the question as to whether or not this anti-education scenario is truly the norm. Is higher education helpful or not in getting funded? Using data from a large startup competition, where some startups ultimately get funded and others do not, we have the required treatment and control groups to be able to shed light on that research question. A primary impact of this paper is that it shows academics, founders and investors that education level is a positive factor in getting funded. A secondary impact is that there appears to be a negative curvilinear relationship between years of education and funding success. This means that there may be an optimal level of education after which additional education no longer helps attract professional investors, but may actually begin to be an impediment.
Keywords: G24; J24; L26; M13; 330; Startups; education; venturecapital; human capital; entrepreneurial finance; angel investing